“Generalis hypotheca est modici praeiudicii”: The adaptation of late medieval ius commune doctrine on the enforcement of obligations to contemporary legal practice - Ilya A. Kotlyar (Clio@Themis)
Debt enforcement is always an area of law of great practical importance, and the European Middle Ages were not an exception in this regard. A lot of attention has been dedicated to the technicalities of debt enforcement in France, Italy, the Low Countries, etc. And yet, not enough attention has been paid to the ways in which the medieval learned doctrine was being adapted to the legal practice. Executive pacts, non-alienation clauses, excussio bonorum, constitutum possessionis – these topics were seen as a “matter of everyday importance”. This article explores how the juxtaposition of general and special hypothec arose in the works of medieval learned jurists and argues that it was inspired by the legal practice of contemporary Italy and France.